Terapi Pijat Tangan dan Minuman Herbal Jahe Madu untuk Ibu Hamil dengan Mual Muntah - Dewi Nurlaela Sari; Anri Anri (STIKes Hang Tuah Pekanbaru, 2021)
Nausea and vomiting are some of the discomforts of pregnancy that can interfere and cause complications. The care provided to overcome nausea and vomiting can be carried out with pharmacological and non-pharmacological approaches. Non-pharmacological therapies that can be developed to reduce nausea and vomiting are hand massage and the provision of herbal drinks. So that nausea and vomiting care can be done both internally and externally. The purpose of this study was to determine the effect of giving hand massage therapy and ginger herbal drink to pregnant women with 1st-trimester nausea and vomiting. The type of method used was quasi-experimental with a pre-post test design. The sample was divided into 2 groups, namely the control group and the treatment group. Sampling by Randomized Controlled Clinical Trials (RCT). The number of samples is 30 respondents for each group so that the total number of respondents is 60 people. The instrument used is Pregnancy-Unique Quantification Of Emesis/Nausea (PUQE). The research was conducted for 3 months, The type of univariate analysis uses a frequency distribution and bivariate analysis uses the Wilcoxon Signed Rank Test analysis. The results showed that the intervention was effective as seen from the difference in the decrease in the intensity of nausea and vomiting in pregnant women and the p-value 0.000 < from the alpha value (0.05). The conclusion is, there is a significant effect between those who are given Hand Massage Therapy and Consumption of herbal drinks with those who are not given treatment on the discomfort of nausea and vomiting in pregnant women. Based on the research above, hand massage and herbal drink therapy can be applied as a treatment for nausea and vomiting in pregnant women.